Affective Education Assessment in Islamic Religious Education - Mukhlisin, Mukhlisin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study describes the affective assessment carried out by Islamic Religious Education teachers at MAN Palopo. The study used qualitative with data sources from the head of the school, Islamic Religious Education Teachers, and Students. The results of the study showed that affective education in MAN Palopo is stated in the curriculum and things that can reflect affective education that can be a good school culture, so that affective education will also bring a good school culture and in accordance with the vision and mission of the school. A clear vision and mission are the basis for the vision of MAN Palopo, namely to form intelligent humans who have good morals and akhlakul karimah. In other words, humans who have good morals are humans who maintain a balance between their rights and obligations in their relationship with Allah as their God, their relationship with other humans, and their relationship with the universe.Teachers carry out affective assessments using a categorization system carried out by teachers with four predicates.The affective assessment model at MAN Palopo uses a Likert scale with the predicates "very good, good, quite good and less good" which are in accordance with the predetermined criteria